2018
DOI: 10.1371/journal.pone.0195896
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vaping topography in relation to adherence to exclusive electronic cigarette use in veterans

Abstract: BackgroundUnderstanding vaping patterns of electronic cigarette (EC) use is important to understand the real-life exposure to EC vapor. Long term information on vaping topography in relation to tobacco cigarette (TC) smoking cessation success has not been explored.MethodsObservational non-blinded study where active TC smokers were asked to replace TC with EC over 4 weeks (replacement phase, RP) followed by exclusive EC use for an additional 12 weeks (maintenance phase, MP). TC use and EC compliance was monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…These same smokers also were able to achieve cotinine levels similar to their baseline level once they completely switched over to e-cigarette use. 39 These results, in combination with others, 920 demonstrate that e-cigarette-naïve cigarette smokers and ecigarette-experienced users likely alter puff duration to titrate their nicotine intake. In order for product regulation to account for user behaviour, e-cigarette designs would need to allow for puff durations that lead to sufficient nicotine delivery yet limit compensatory puffing behaviour and increases in temperatures known to produce volatile aldehydes and other toxicants.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These same smokers also were able to achieve cotinine levels similar to their baseline level once they completely switched over to e-cigarette use. 39 These results, in combination with others, 920 demonstrate that e-cigarette-naïve cigarette smokers and ecigarette-experienced users likely alter puff duration to titrate their nicotine intake. In order for product regulation to account for user behaviour, e-cigarette designs would need to allow for puff durations that lead to sufficient nicotine delivery yet limit compensatory puffing behaviour and increases in temperatures known to produce volatile aldehydes and other toxicants.…”
Section: Discussionmentioning
confidence: 54%
“…619 This finding supports recent work in which cigarette smokers were asked to switch to e-cigarette use exclusively within a 4-week period. 39 In that study, those who were successful had significantly longer puff durations than those who were not, and participants had increased puff durations over time as they became more familiar with the e-cigarette product. These same smokers also were able to achieve cotinine levels similar to their baseline level once they completely switched over to e-cigarette use.…”
Section: Discussionmentioning
confidence: 90%
“…The smoking habits of e-cigarettes are typically different than tobacco cigarettes. This stems from the differences in delivery of active substance (nicotine) and compensatory mechanism by either increasing the puff time or frequency of puffing. , Studies have shown that the ultimate goal of changing puff habits are driven by achieving the desired nicotine/cotinine level in a biological system. , To accommodate for differences in smoking habits, all data are normalized to a common measure, i.e., mass of TPM produced and all data reflect content of subject chemical/species per unit mass of TPM. It is possible, thanks to the fact that emission profile of e-cigarettes does not vary much depending on the time of puffing as it is controlled electronically .…”
Section: Methodsmentioning
confidence: 99%
“…EC users can instinctively modulate their behavior, including puff frequency, puff duration, and intervals between EC sessions to achieve their desired nicotine exposure levels. Smokers transitioning to ECs modulate their usage patterns to recapitulate the nicotine delivery profile of cigarettes; this differs from EC users with no prior history of smoking [2,3]. Therefore, properly controlling for the variation present across all facets of EC use is challenging in clinical studies.…”
Section: Ec Studies: Flavor and Device Market Populations Of Interest Preclinical Study Design And Current Challengesmentioning
confidence: 99%